Expanding the meaning of citizenship: "evacuation" of people with disabilities in Russia from the institutions during COVID-19 - Battalova, Alfiya (Disability Studies Quarterly, 2021)
In the wake of COVID-19, non-profit organizations that focus on providing social support services in Russia consolidated their efforts to take proactive measures to change internaty 1, the system of institutions for people with physical, mental, and intellectual disabilities. As a result of advocacy efforts by the non-profit organizations, 26 people from these institutions were evacuated and provided with temporary assisted housing. The decision to act proactively to prevent the spread of the virus among the residents of the institutions is indicative of the galvanized efforts of the non-profit sector to advocate for deinstitutionalization and assisted living. COVID-19 served as an opportunity for the non-profit organizations to emphasize the need for expediting deinstitutionalization reform. Drawing on media sources, the literature on disability and advocacy in Russia, and the conceptual framework of citizenship, this paper will provide an overview of the internaty system, analyze the legislative context of disability and COVID-19, and discuss the context of deinstitutionalization advocacy in Russia.